A comprehensive review of the utilization of alternative binding properties in the construction of asphalt pavements - Ferdaus, R.; Khairil Azman, Masri; Hasan, Kamrul; Putra Jaya, Ramadhansyah (Elsevier Ltd., 2025)
Asphalt pavement construction has traditionally relied on conventional binders; however, growing concerns over environmental sustainability and performance have catalyzed a shift towards exploring alternative binders. This paper presents a thorough review of the burgeoning impact of alternative binders in asphalt pavement construction. Investigated alternative binder properties include polymers, waste cooking oil (WCO), waste engine oil (WEO), resin, and others, all of which show promise as modified asphalt binders. The review underscores the potential of alternative binders to transform asphalt pavement construction, offering sustainable, cost-effective, and high-performance solutions. Benefits include reduced reliance on fossil fuels, enhanced durability, improved rutting resistance, and a diminished environmental footprint. Moreover, the paper emphasizes the necessity for ongoing research and collaboration among researchers, practitioners, and policymakers to fully relalize the advantages of alternative binder properties in fostering greener and more resilient transportation infrastructure. This research signals a pivotal shift towards environmentally conscious practices in pavement construction, focusing on sustainable solutions to meet contemporary infrastructure demands while minimizing ecological impacts.